2020
DOI: 10.1093/infdis/jiaa476
|View full text |Cite
|
Sign up to set email alerts
|

School-Based Serosurveys to Assess the Validity of Using Routine Health Facility Data to Target Malaria Interventions in the Central Highlands of Madagascar

Abstract: Background In low-malaria-transmission areas of Madagascar, annual parasite incidence (API) from routine data has been used to target indoor residual spraying at sub-district commune levels. To assess validity of this approach, we conducted school-based serological surveys and health facility (HF) data quality assessments in seven districts to compare API to “gold-standard” commune-level serological measures. Methods At two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Despite the lack of a clearly defined relationship between antigen-matched targets from opposing expression systems, we remain confident that microarrays utilising IVTT or purified recombinant proteins are able to produce compelling and biologically relevant data. Indeed, our data show age-dependent trends in antibody responses (typical of highly endemic populations [1][2][3]) irrespective of expression system (Supplementary figure 2), lending weight to the applicability of either methodology in serological assays [33][34][35][36][37][38][39][40][41][42][43][44][45][46].…”
Section: Ama1 -Ivtt_1mentioning
confidence: 56%
“…Despite the lack of a clearly defined relationship between antigen-matched targets from opposing expression systems, we remain confident that microarrays utilising IVTT or purified recombinant proteins are able to produce compelling and biologically relevant data. Indeed, our data show age-dependent trends in antibody responses (typical of highly endemic populations [1][2][3]) irrespective of expression system (Supplementary figure 2), lending weight to the applicability of either methodology in serological assays [33][34][35][36][37][38][39][40][41][42][43][44][45][46].…”
Section: Ama1 -Ivtt_1mentioning
confidence: 56%
“…Studies for the detection of antibodies against Plasmodium MSP1 proteins are increasingly used to map geographical distributions, seroprevalence and transmission intensities of malaria infection [22][23][24]. The C-terminal portion of the merozoite surface protein 1 (MSP1 19 ) is a promising candidate for the malaria vaccine, as it is highly immunogenic [25,26], therefore being extensively analyzed as an immunological target in many studies [23,[25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, capillary blood was collected for all children in microvette tubes (Microvette 500 Z-Gel; Sarstedt) for later serological analyses. Collected samples were transported to Institut Pasteur de Madagascar’s immunology laboratory in Antananarivo and stored at − 20 °C until used [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…In 2014, a cross-sectional school-based survey was carried out in seven districts of the CHL and surrounding Fringes areas to better characterize malaria transmission via use of serological markers of P. falciparum exposure [ 11 ]. Results showed that the ability of annual parasite incidence estimates using health facility routine data of malaria-confirmed patients by RDT to characterize malaria transmission declined at lower transmission levels as compared with a serological approach [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation